Coronavirus nucleocapsid proteins: a multifaceted modulator in the innate immune evasion - Xiao, Yuting; Song, Ziyao; Zhou, Lei; Lu, Wanqing; Fang, Weihuan; Xu, Jidong; Li, Xiaoliang (Frontiers in Microbiology, 2025)
Coronaviruses are capable of inducing diverse infectious diseases that pose significant threats to the public health and the economic development. With a single positive-stranded RNA genome, coronaviruses utilize viral proteins to execute diverse immune escape strategies to facilitate their replication. Of all the identified structural proteins and non-structural proteins within the coronaviruses, nucleocapsid (N) protein is highly conserved and is the most abundant viral protein in infected host cells. N protein regulates the more complex and diverse mechanisms through which viruses suppress host immunity. In this review, we analyzed the basic structure of coronavirus N protein, and further elaborate on its multifaceted regulatory functions in the virion assembly, pathogenesis, host innate immune responses, as well as the innate immunity-related programmed cell death and cell cycle, and also other cell processes. A better understanding of the immune evasion strategy regulated by N protein will help to provide a theoretical basis for the development of broad-spectrum anti-coronavirus drugs targeting N proteins.